2015
DOI: 10.1021/acsmacrolett.5b00601
|View full text |Cite
|
Sign up to set email alerts
|

Imidazole Derivatives with an Intramolecular Hydrogen Bond as Thermal Latent Curing Agents for Thermosetting Resins

Abstract: Epoxy resins are important thermosetting resins widely used in industrial applications. Though imidazoles as curing agents have attracted particular attention because of their high reactivity in chain polymerizations with epoxides, polymerization of a liquid epoxy resin containing imidazoles proceeds gradually even at room temperature. This makes it difficult to use such mixtures as one-component materials for industrial applications. To improve the shelf life of the mixutures, we have developed a very simple … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
50
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 65 publications
(51 citation statements)
references
References 19 publications
1
50
0
Order By: Relevance
“…Epoxy resin compositions containing ionic liquids had long‐term storage stability and good curability around 150 °C, although some needed higher temperatures (above 200 °C) for activation. On the other hand, our group has also proposed a thermal latent curing agent where the nucleophilicity of an imidazole ring is suppressed by intramolecular hydrogen bonding . The agent is compatible with conventional epoxy resins and shows good curability as well as long‐term storage stability.…”
Section: Methodsmentioning
confidence: 99%
“…Epoxy resin compositions containing ionic liquids had long‐term storage stability and good curability around 150 °C, although some needed higher temperatures (above 200 °C) for activation. On the other hand, our group has also proposed a thermal latent curing agent where the nucleophilicity of an imidazole ring is suppressed by intramolecular hydrogen bonding . The agent is compatible with conventional epoxy resins and shows good curability as well as long‐term storage stability.…”
Section: Methodsmentioning
confidence: 99%
“…By contrast, our group has proposed another liquid‐type thermal latent curing agent where retro ‐Michael addition reactions are used to generate imidazoles . Furthermore, our group has also reported that 2‐(2‐hydroxyphenyl)imidazole derivatives work as a thermal latent curing agent, which is compatible in conventional epoxy resins and shows good curability and superior storage stability …”
Section: Introductionmentioning
confidence: 99%
“…These results indicate that the polarity around 1 would largely influence its hydrolysis. Therefore, we considered that if the polarity were increased by generation of hydroxy groups or alkoxylates in an epoxy curing system, in situ generation of the imidazole derivative 2 having high curability from 1 would be accerelated …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The blocking of the active groups (such as amines, thiols, and phenols) of hardeners with thermally removable groups (Fig. 1b)17181920212223 is the main approach for achieving the liquid latent system. Sometimes, these methods may induce sluggish liberation of the active groups, resulting in slow curing processes that are undesirable in commercial uses.…”
mentioning
confidence: 99%